Sustaining Competitiveness in a Commodity Market - Tan, Fonn Hwee Beng (2006)
In this research project, a study on how Sasol, an oil and chemicals producers, evaluate the issues that the company could consider as precursors to sustain its competitiveness in the commodity market. Six independent variables being; Price Competitiveness, Customer Satisfaction, Service Efficiency, Relationship Management, Customer loyalty, Technology have been used to determine its relation with sustainability. In this project, a measurement of the intangibility of resources, customer loyalty as well as determination of the correlation between customer satisfaction and customer loyalty will also be illustrated.